Beaver at Frame Lake - Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
We watched this beaver swim all the way to the north side of the lake to a stand of rushes.We were able to come close enough to see that it was eating on a poplar branch rather than the rushes. We could clearly see the beaver using its paws to hold the branch and also to push leaves and bark into its mouth. ...